Redox-Related Neuronal Death and Crosstalk as Drug Targets: Focus on Epilepsy - Mao, Xiao-Yuan; Zhou, Hong-Hao; Jin, Wei-Lin (Frontiers in Neuroscience, 2019)
Cell death has a vital role in embryonic development and organismal homeostasis. Biochemical, pharmacological, behavioral and electrophysiological evidences support the idea that dysregulation of cell death programs are involved in neuropathological conditions like epilepsy. The brain is particularly vulnerable to oxidative damage due to higher oxygen consumption and lower endogenous antioxidant defense than other bodily organ. Thus, in this review, we focused on the comprehensive summarization of evidence for redox-associated cell death pathways including apoptosis, autophagy, necroptosis and pyroptosis in epilepsy and the oxidative stress-related signaling in this process. We specially proposed that the molecular crosstalk of various redox-linked neuronal cell death modalities might occur in seizure onset and/or epileptic conditions according to the published data. Additionally, abundance of polyunsaturated fatty acids in neuronal membrane makes the brain susceptible to lipid peroxidation. This presumption was then formalized in the proposal that ferroptosis, a novel type of lipid reactive oxygen species (ROS)-dependent regulatory cell death, is likely to be a critical mechanism for the emergence of epileptic phenotype. Targeting ferroptosis process or combination treatment with multiple cell death pathway inhibitors may shed new light on the therapy of epilepsy.